Spatial Dynamics of Specialized and Sophisticated Small and Medium-Sized Enterprises on New High-Quality Productive Forces from an Evolutionary Economic Geography Perspective - Huibo Zhong; Mingwei Chu; Yuhang Xia; Keyu Zhai; Xing Gao (Land)
Amidst global economic stagnation, China is undergoing a significant economic transformation by fostering new high-quality productive forces (NHPFs). In this transformative context, specialized and sophisticated small and medium-sized enterprises (SpecSof SMEs) play a critical role. This paper develops a framework from an evolutionary economic geography (EEG) perspective to analyze how these SMEs influence NHPFs. The study assesses the impact of specialized and sophisticated SMEs on NHPFs using OLS and addresses potential endogeneity issues through the application of instrumental variables. The results show that the Specialized and Sophistication Index (SSI) positively impacts NHPFs, with its effect strengthening from the company to the municipal level (by about 25%) but weakening at the provincial and national levels (to half of the municipal level), highlighting a clear marginal effect on regional NHPFs. Additionally, the geographically weighted regression (GWR) model was employed to investigate the complex and spatially varied relationships between key characteristics of specialized and sophisticated SMEs and NHPFs. Our findings suggest that while the relationship between SSI and NHPFs is generally positive, it is spatially heterogeneous, arising from variations in regional economic structures, market maturity, and industrial characteristics. This study provides a theoretical framework for understanding regional disparities in NHPF development through SpecSof SMEs and offers empirical evidence to inform region-specific policies and spatial planning strategies.